2022
DOI: 10.1007/s12517-022-09986-4
|View full text |Cite
|
Sign up to set email alerts
|

Air and water health: industrial footprints of COVID-19 imposed lockdown

Abstract: Overall lockdown limitations toward the start of the year 2020 are credited to the annihilation and fatalities worldwide because of COVID-19. Most of the nations revealed rapid growth of COVID-19 cases and subsequently declared lockdown in several stages. Because of these lockdowns, industries had to stop producing goods other than the actual merchandise needed to survive. The air quality and natural water quality witnessed a noticeable improvement from limited human activity. This paper presents an investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Bonnevie et al [27] measured the opposition to the COVID-19 vaccine with the Twitter dataset. Recent research performed prediction [28], environmental [29], health [30,31], socioeconomic [32], emotional [33] impact of COVID-19. Iwendi et al [34] suggested a new strategy to detect fake news related to COVID-19.…”
Section: Sentiment Analysismentioning
confidence: 99%
“…Bonnevie et al [27] measured the opposition to the COVID-19 vaccine with the Twitter dataset. Recent research performed prediction [28], environmental [29], health [30,31], socioeconomic [32], emotional [33] impact of COVID-19. Iwendi et al [34] suggested a new strategy to detect fake news related to COVID-19.…”
Section: Sentiment Analysismentioning
confidence: 99%
“…The fractional fuzzy models created to analyze the COVID problems through the fractional techniques [25] , [26] , [27] , [28] , [29] . The researchers works on COVID-19 in various categories like detection [30] and prediction [31] of COVID-19 using deep learning, IoT technology for medical advice [32] and the interrelation between the lockdown and the air and water quality during the pandemic [33] . Therefore, by collaborating the fuzzy MCDM methods, this work proposes a integrated MCDM method, which could perform different tasks in the proposed algorithm.…”
Section: Introductionmentioning
confidence: 99%